Upaya Pemenuhan Hak Alimentasi Bagi Orang Tua Lansia Terlantar Di Panti Jompo Griya Lansia “Jannati” - Siti Nurmilawaty Tuliyabu; Mutia Ch. Thalib; Dolot Alhasni Bakung (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study aims to find out about how the efforts to fulfill the right of alimony from children to parents who are entrusted in nursing home Griya Lansia “Jannati”. The method used in this study is empirical with qualitative descriptive data analysis that describes and outlines the data and facts of the field. The results of this study showed that the effort to fulfill the right of alimony for the elderly in the nursing home Griya Lansia “Jannati” is not optimal, this is because children do not carry out their obligations in fulfilling the rights of alimony that should be obtained by parents who are in the nursing home Griya Lasia “Jannati”. The child fulfills only a small part of the alimony rights that parents should have. For example, children only provide a living when visiting Within 2 months, and children only visit their parents regularly so that parents feel lonely and abandoned.